Welcome - TTHR (The Toro Historical Review, 2024)
Welcome to volume 15, issue 1 of The Toro Historical Review! Congratulations to the authors: Jasmin Aguilar, Efrain Contreras, Alexander Gonzalez, Michael Gonzalez, and Luis Murillo. And a special thank you to our editorial team who has worked hard to bring this issue to fruition. Thank you! This issue features five essays produced in upper-division history classes and represents remarkable achievements in undergraduate research, writing, and editing. Well done all!